Computer Security c - Fournaris, Apostolos P.; Athanatos, Manos; Lampropoulos, Konstantinos; Ioannidis, Sotiris; Hatzivasilis, George; Damiani, Ernesto; Abie, Habtamu; Ranise, Silvio; Verderame, Luca.; Siena, Alberto; Garcia-Alfaro, Joaquin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book constitutes the refereed post-conference proceedings of the Second International Workshop on Information & Operational Technology (IT & OT) security systems, IOSec 2019 , the First International Workshop on Model-driven Simulation and Training Environments, MSTEC 2019, and the First International Workshop on Security for Financial Critical Infrastructures and Services, FINSEC 2019, held in Luxembourg City, Luxembourg, in September 2019, in conjunction with the 24th European Symposium on Research in Computer Security, ESORICS 2019. The IOSec Workshop received 17 submissions from which 7 full papers were selected for presentation. They cover topics related to security architectures and frameworks for enterprises, SMEs, public administration or critical infrastructures, threat models for IT & OT systems and communication networks, cyber-threat detection, classification and pro ling, incident management, security training and awareness, risk assessment safety and security, hardware security, cryptographic engineering, secure software development, malicious code analysis as well as security testing platforms. From the MSTEC Workshop 7 full papers out of 15 submissions are included. The selected papers deal focus on the verification and validation (V&V) process, which provides the operational community with confidence in knowing that cyber models represent the real world, and discuss how defense training may benefit from cyber models. The FINSEC Workshop received 8 submissions from which 3 full papers and 1 short paper were accepted for publication. The papers reflect the objective to rethink cyber-security in the light of latest technology developments (e.g., FinTech, cloud computing, blockchain, BigData, AI, Internet-of-Things (IoT), mobile-first services, mobile payments).
Information & Operational Technology (IT & OT) security systems (IOSec 2019) -- Model-driven Simulation and Training Environments (MSTEC 2019) -- Security for Financial Critical Infrastructures and Services (FINSEC 2019).
Keywords: Computer security; Computers; Computer organization; Computer crimes; Law and legislation; Data encryption (Computer science).; Systems and Data Security; Information Systems and Communication Service; Computer Systems Organization and Communication Networks; Computer Crime; Legal Aspects of Computing; Cryptology